Hilbert–Huang transform‐based transient busbar protection algorithm. Issue 14 (1st November 2015) - Guo, Zhenwei; Yao, Jiangang; Tan, Zhewen
Abstract : A new algorithm for busbar protection is proposed based on the Hilbert–Huang transform in this study. The algorithm decomposes currents of all lines connecting to the busbar into intrinsic‐mode functions and calculates the instantaneous amplitude of the first intrinsic mode function (IMF). Then, the instantaneous amplitude is normalised to eliminate the impact of fault initial angle and transition resistance. When a fault occurs on the busbar, the initial travelling waves on head ends of the lines all have great instantaneous amplitudes; when a fault occurs on any line, the travelling wave on the faulted line is of great instantaneous amplitude, whereas the initial travelling waves on healthy lines are of small instantaneous amplitudes. Thus, through analysing the detected instantaneous amplitudes of travelling waves, a new busbar protection scheme can be constructed, which achieves a high reliability relative to other fault‐travel‐wave‐based algorithms. According to simulation results on a 500 kV substation modelled in ATP‐Draw, the graphical preprocessor to ATP‐EMTP windows version, the proposed algorithm is effective in determining various types of faults.